Modification Optimization and Contact Analysis of Helical Gear - Wang Huimin; Wu Xuncheng; Zhang Yanjie (Jixie chuandong)
Based on principles of gear meshing,the precise 3D parametric model of the involute gear is built by using UG,and the finite element model of five teeth is established according to the contact analysis theory,and the contact analysis of simplified model is completed by ANSYS Workbench. Changing the traditional empirical modification method and the software KISSsoft is used to carry out optimization design of gear modification parameters according to the results of finite element analysis. The tooth surface contact intensity and transfer error are taken as the optimization target to obtain the optimal modification values and the modification result is finally verified through the ANSYS Workbench.